Patient reported evaluation of functional symptoms (PREFS): a simple method of ascertaining patient satisfaction post cataract surgery - Waqar, S; Holdstock, C; Evans, N (Nepalese Journal of Ophthalmology, 2012)
No abstract available.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6562 Nepal J Ophthalmol 2012; 4 (2): 346-347